Galactic Cosmic Radiation in the Interplanetary Space Through a Modern Secular Minimum - F. Rahmanifard; W. C. deWet; N. A. Schwadron; M. J. Owens; A. P. Jordan; J. K. Wilson; C. J. Joyce; H. E. Spence; C. W. Smith; L. W. Townsend (Space Weather)
Abstract Recent solar conditions indicate a persistent decline in solar activity—possibly similar to the past solar grand minima. During such periods of low solar activity, the fluxes of galactic cosmic rays (GCRs) increase remarkably, presenting a hazard for long‐term crewed space missions. We used data from the Cosmic Ray Telescope for the Effects of Radiation (CRaTER) on the Lunar Reconnaissance Orbiter (LRO) to examine the correlation between the heliospheric magnetic field, solar wind speed, and solar modulation potential of the GCRs through Cycle 24. We used this correlation to project observations from past secular solar minima, including the Dalton minimum (1790–1830) and the Gleissberg minimum (1890–1920), into the next cycle. For the case of conditions similar to the Dalton (or Gleissberg) minimum, the heliospheric magnetic field could drop to 3.61 (or 4.06) nT, leading to a dose rate increase of ∼75% (or 34%). We showed that accounting for a floor in the modulation potential, invoked by the Badhwar‐O'Neill 2014 model, moderates the projected radiation levels in Cycle 25. We used these results to determine the most conservative permissible mission duration (PMD, 290.4−35.9+37.7 and 204.3−25.2+26.6 days for 45‐year‐old male and female astronauts, respectively) based on a 3% risk of exposure‐induced death (REID) at the upper 95% confidence interval in interplanetary space.